An Unusual Case of Synchronous Carcinoid of Ovary and Gall Bladder - Rupali Bassi; Raksha Arora; Sangeeta Bhasin; Nita Khurana (Case Reports in Obstetrics and Gynecology)
Multifocal carcinoid is a known phenomenon. We present a rare combination of an ovarian carcinoid synchronous with gallbladder carcinoid. This rare combination has not been reported so far. An asymptomatic 45-years-old perimenopausal lady was diagnosed to have a metastatic ovarian cancer, but on laparotomy she was found to have a primary synchronous metastatic gall bladder as well. On histopathological evaluation she was found to have two separate primary carcinoids. Subsequently the patient received chemotherapy and is completely asymptomatic on follow up. Further research needs to be undertaken and guidelines need to be formulated for management of these cases.